Cognitive and quality‐of‐life related factors of body mass index (BMI) improvement after deep brain stimulation in the subcallosal cingulate and nucleus accumbens in treatment‐refractory chronic anorexia nervosa. (23rd March 2022) - Pérez, Víctor; Villalba‐Martínez, Gloria; Elices, Matilde; Manero, Rosa María; Salgado, Purificación; Ginés, José María; Guardiola, Rocío; Cedrón, Carlos; Polo, María; Delgado‐Martínez, Ignacio; Conesa, Gerardo; Medrano, Santiago; et al.
Abstract: Background: Up to 20% of the cases of anorexia nervosa (AN) are chronic and treatment‐resistant. Recently, the efficacy of deep brain stimulation (DBS) for severe cases of AN has been explored, with studies showing an improvement in body mass index and other psychiatric outcomes. While the effects of DBS on cognitive domains have been studied in patients with other neurological and psychiatric conditions so far, no evidence has been gathered in AN. Methods: Eight patients with severe, chronic, treatment‐resistant AN received DBS either to the nucleus accumbens (NAcc) or subcallosal cingulate (SCC; four subjects on each target). A comprehensive battery of neuropsychological and clinical outcomes was used before and 6‐month after surgery. Findings: Although Body Mass Index (BMI) did not normalise, statistically significant improvements in BMI, quality of life, and performance on cognitive flexibility were observed after 6 months of DBS. Changes in BMI were related to a decrease in depressive symptoms and an improvement in memory functioning. Interpretation: These findings, although preliminary, support the use of DBS in AN, pointing to its safety, even for cognitive functioning; improvements of cognitive flexibility are reported. DBS seems to exert changes on cognition and mood that accompany BMI increments. Further studies are needed better to determine the impact of DBS on cognitive functions. Highlights: Although body mass index (BMI) did not normalise, statistically significant improvements in BMI, quality of life, and performance on cognitive flexibility were observed after 6 months of continuous DBS stimulation either to the nucleus accumbens or subcallosal cingulate An increase in BMI was related to a decrease in depressive symptoms and an improvement in memory functioning These preliminary findings suggest that DBS is not associated with any cognitive deterioration in people with AN